Winnie flies again - Thomas, Valerie; Paul, Korky (Oxford : Oxford University Press, 2001)
Winnie the witch has trouble navigating crowded skies, so she tries changing her broomstick into other means of transportation, until she discovers what she really needs.
"Originally published in England in 1999 by Oxford University Press"--P. facing t.p.
Publisher's Weekly
School Library Journal
2.0
K-3.
K-3
Keywords: Eyeglasses -- Fiction; Humorous stories; Witches -- Fiction; Eyeglasses -- Fiction; Humorous fiction; Witches -- Fiction